The microstructural development and erosion mechanism of BaZrO3/Al2O3 double ceramics by Ti–46Al–8Nb alloy melt - Lu Mao; Qisheng Feng; Xingguang Jin; Haitao Li; Baohua Duan; Dongdong He; Mingrui Lv; Pengyue Gao; Xinmei Hou; Guangyao Chen; Chonghe Li (Journal of Materials Research and Technology)
In this study, the erosion of BaZrO3/Al2O3 double ceramics by Ti–46Al–8Nb alloy melt was investigated at different melting temperatures (1833 K, 1873 K and 1913 K) and time (1800 s, 3600 s, 5400 s and 7200 s). The microstructure of erosion layer and the alloy ingot were analyzed as well as the oxygen content of the alloy ingot. The erosion mechanism was clarified in the kinetic perspectives. The results showed that the new oxide BaAl2O4 production was attached on the ingot surface, and two kinds of inclusions, i.e., (Ti, Zr)5(Si, Al)3 and YAlO3, were formed in the ingot matrix. The thickness of erosion layer, the oxygen content of ingot, and the volume fraction of inclusions increased with increasing melting temperatures and time. In addition, these three phenomena were controlled by the kinetics of dissolution, and the time exponents were approximately equaled to 0.5, indicating that the erosion mechanism was dissolution controlled by mutual diffusion between the double ceramics and alloy melts. The activation energies of three phenomena were determined by Arrhenius equation, and three kinetic models were further established.